PARTISIPASI MASYARAKAT DALAM TAHAP PENGEMBANGAN DESA WISATA KEMETUL - ., Ignasius; Susilowati, Linda (KRITIS, 2020)
The Development village as tourist destination requires local community participation. However, sometimes community involvement is neglected by many people. This study aims to analyze the participation of local communities in the development of Kemetul Village as tourist destination. Kemetul Village is located in Semarang Regency, Central Java. This research is conducted by using in-depth interview and observation to the public, managers, and other parties involved. The analytical method used is a qualitative method. The research found that community participation in the development of Kemetul Tourism village can be seen from their involvement in these stages: the preparation stage, the program planning stage, the operational stage, the development stage, the monitoring stage and the community evaluation program. The community participation also faces some challenges such as lack of understanding concept of a tourism village, people assumption about lack of benefit from a tourism village, some local people do not care about tourist village development, the difficulty of arranging an appropriate time for the community to involve in activities or programs, and lack of initiatives from the manager and local government on involving the people of Kemetul Village.